Risiko kebakaran dan ledakan di depot bahan bakar minyak yang sudah lama berdiri: implikasi komunikasi risiko bagi pekerja dan penduduk sekitar untuk mengantisipasi kedaruratan - Arifin Jati Sukma; Rochim Bakti Cahyono (Berita Kedokteran Masyarakat (BKM), 2018)
Risks of fire and explosion in long-standing fuel oil depots: risk communication implications for workers and local residents to anticipate emergenciesPurpose: Fires and explosions in oil depots remain occur even though large oil companies have set up occupational health and safety system. Negligence of monitoring and no re-evaluation of conditions and situations from the plants are among common explanations. This study evaluates the potential for explosions and fires from a long-standing oil depot, including the potential impact on workers and residents around the site.Method: The study was conducted at the Pertamina Rewulu depot in Kulon Progo. Data were analyzed using the Dow's Fire and Explosion Index method, Point Source Radiation Model, and Gaussian Dispersion. In-depth interviews were conducted with respondents from contract workers and local resident closed to the plant.Result: Calculations from the data indicate that there are potential hazards that were not anticipated before the research was planned. All tanks from the Class A category have a 'medium' danger level. Based on the simulation, if there is a large fire at this depot, CO levels are estimated not to give danger when smoke reaches the neighborhood. The study also found that although the depot has been established for more than 40 years, residents who now live in the vicinity of the depot have not received fire risk information and communication about emergency preparedness from the management.Conclusion: Recurrent evaluations of the risk of explosion and fire in long-standing fuel depots show previously unanticipated findings Regular risk communication to contract workers and surrounding residents who change is needed so that they have preparedness to respond to the dangers of smoke from explosions and fires.